Gene Expression in Nitrogen-Fixing Symbiotic Nodule Cells in Medicago truncatula and Other Nodulating Plants. Issue 1 (11th November 2019) - Mergaert, Peter; Kereszt, Attila; Kondorosi, Eva
Abstract : Gene expression analyses of nodules of the nitrogen-fixing clade of plants have advanced our understanding of nodule organogenesis and functioning and the evolution of symbiosis. Abstract: Root nodules formed by plants of the nitrogen-fixing clade (NFC) are symbiotic organs that function in the maintenance and metabolic integration of large populations of nitrogen-fixing bacteria. These organs feature unique characteristics and processes, including their tissue organization, the presence of specific infection structures called infection threads, endocytotic uptake of bacteria, symbiotic cells carrying thousands of intracellular bacteria without signs of immune responses, and the integration of symbiont and host metabolism. The early stages of nodulation are governed by a few well-defined functions, which together constitute the common symbiosis-signaling pathway (CSSP). The CSSP activates a set of transcription factors (TFs) that orchestrate nodule organogenesis and infection. The later stages of nodule development require the activation of hundreds to thousands of genes, mostly expressed in symbiotic cells. Many of these genes are only active in symbiotic cells, reflecting the unique nature of nodules as plant structures. Although how the nodule-specific transcriptome is activated and connected to early CSSP-signaling is poorly understood, candidate TFs have been identified using transcriptomic approaches, and the importance of epigenetic and chromatin-based regulation has been demonstrated. We discuss how gene regulation analyses have advanced our understanding of nodule organogenesis, the functioning of symbiotic cells, and the evolution of symbiosis in the NFC.